Analisis Proses Bisnis Departemen Warehouse & Logistic Menggunakan Metode BPI pada Perusahaan Manufaktur - Mulyana, Andi Erna; Soleha, Dinda Fauziah Annisa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
The objective of this investigation is to assess the alignment of manufacturing company operations with the standards outlined in ISO 9001:2015, and subsequently modify organizational protocols to adhere to these standards. Business Process Improvement (BPI) methodology is employed as a framework to facilitate the examination, supplemented by the DMAIC approach for in-depth analysis. Utilizing the DMAIC methodology yields protocols that conform to the ISO 9001:2015 criteria, particularly focusing on the clauses pertaining to Product Identification and Traceability procedures. Amendments are implemented by incorporating the material delivery process flow and requisite control mechanisms to ensure the traceability of materials/subparts back to the company. Findings from this study indicate a necessity for procedural enhancements, specifically the inclusion of subcontractor preparation and workflow delineation, alongside adjustments to existing protocols to align with ISO 9001:2015 stipulations.